Effect of line length to voltage sag propagation by monitoring the behaviour of phase angle jumps / Nazarohaidayu Mohamed Nasir - Mohamed Nasir, Nazarohaidayu (2014)
Occurrences of voltage sag in power system are one of the most major concerns in power quality problem. Power system faults are the largest contributors to voltage sag and phase angle jumps. Three essential characteristics that voltage sag is commonly described which are sag magnitude (voltage during the fault), sag duration and frequency. Power system network consists of different transformer windings configurations and different line length. During fault, transformers winding configuration and line length may affect the propagation of phase angle jumps in a power system network. Thus the intention of this work is to investigate the propagation of faulted voltage to other busbar under an influence of the transformer connections and the effect of line length impedance to the faulted voltages by monitoring the behaviour of phase angle jumps. Power System Computer Aided Design (PSCAD/EMTDC) will be used to construct and simulate a power system test model network. The test system used will allows major variations in network parameter in order to understand its influence on voltage sag propagation.